Assessing the role of rare genetic variants in drug‐resistant, non‐lesional focal epilepsy. Issue 7 (21st May 2021) - Wolking, Stefan; Moreau, Claudia; McCormack, Mark; Krause, Roland; Krenn, Martin; ,; Berkovic, Samuel; Cavalleri, Gianpiero L.; Delanty, Norman; Depondt, Chantal; Johnson, Michael R.; Koeleman, Bobby P. C.; et al.
Abstract: Objective: Resistance to antiseizure medications (ASMs) is one of the major concerns in the treatment of epilepsy. Despite the increasing number of ASMs available, the proportion of individuals with drug‐resistant epilepsy remains unchanged. In this study, we aimed to investigate the role of rare genetic variants in ASM resistance. Methods: We performed exome sequencing of 1, 128 individuals with non‐familial non‐acquired focal epilepsy (NAFE) (762 non‐responders, 366 responders) and were provided with 1, 734 healthy controls. We undertook replication in a cohort of 350 individuals with NAFE (165 non‐responders, 185 responders). We performed gene‐based and gene‐set‐based kernel association tests to investigate potential enrichment of rare variants in relation to drug response status and to risk for NAFE. Results: We found no gene or gene set that reached genome‐wide significance. Yet, we identified several prospective candidate genes – among them DEPDC5, which showed a potential association with resistance to ASMs. We found some evidence for an enrichment of truncating variants in dominant familial NAFE genes in our cohort of non‐familial NAFE and in association with drug‐resistant NAFE. Interpretation: Our study identifies potential candidate genes for ASM resistance. Our results corroborate the role of rare variants for non‐familial NAFE and imply their involvement in drug‐resistant epilepsy. Future large‐scale genetic research studies are needed to substantiate these findings.